Competition between poly-, pluri- and multi- in official French neologisms - Holeš, Jan (Kalbotyra, 2023)
The article deals with the formation and use of the three prefixes that express plurality in French official terminology, on the example of the 162 terms appearing in FranceTerme and containing the prefixes pluri-, poly- and multi-. Among them, multi- is the most productive (104 terms), followed by poly- (50 terms) and pluri- (8 terms). With regard to the distribution of terms according to the domains, the natural and technical sciences dominate over the social sciences. The comparison with the English equivalents reveals a fairly high correspondence rate, even if 23% of the terms are not constructed in the same way. Relatively frequent substitutions of prefixes between English and French, e.g. pluri- and poly- in French instead of multi- in English, witness about their partial synonymy.
Keywords: term; terminology; prefix; neology; FranceTerme